Penanaman Karakter Religius melalui Metode Pembiasaan pada Siswa SDIT Nurul Islam Tengaran - Wasito Wasito; Mukh. Nursikin (ISLAMIKA, 2023)
This study aims to analyze the cultivation of religious character through the habituation method to SDIT Nurul Islam Tengaran students. This type of research is descriptive qualitative. The research subjects consisted of students from SDIT Nurul Islam Tengaran. Data collection through interviews, observation and documentation. Data analysis techniques through data reduction, data presentation and drawing conclusions. The results of the study show that the cultivation of religious character education at SDIT Nurul Islam Tengaran through the habituation method is reflected in the culture and activities as follows: shaking hands with the teacher in the morning, entering class by saying greetings, praying pre and post lessons, morning tahfid or memorizing al-Qur'an Juz 30-29-28, sunnah dhuha prayers, recite the Koran, perform midday prayers in congregation followed by mentoring and specifically on Fridays there is a BPI (Islamic Personal Development) program.